A rare case of eosinophilic meningitis - Dcruz, Beryl B.; Cherian, Carol Sara; Koshy, Shanty Mary; George, Jewel Maria; Sunnychan, Sebin (International Journal of Contemporary Pediatrics, 2023)
Eosinophilic meningitis is a rare form of meningitis, usually caused by helminthic infection and the most common agent is Angiostrongylus cantonensis. It has a variable clinical presentation that ranges from cranial nerve abnormalities, ataxia, meningitis, encephalitis and rarely death. As the literature and reviews on this topic are rare, the standard treatment for eosinophilic meningitis caused by A. cantonensis infection has always been controversial. There is evidence that a 2-week course of high dose corticosteroid along with albendazole have helped in management. Here we discuss the case of a toddler with eosinophilic meningitis with Angiostrongylus species.